Character Association And Path Analysis Of Exotic Tomato (Solanum Lycopersicum L.) Genotypes - Islam, BMR; Ivy, NA; Rasul, MG; Zakaria, M (Bangladesh Journal of Plant Breeding and Genetics, 2011)
Correlations and path coefficient were studied in 39 exotic tomato (Solanum lycopersicum L.) genotypes for nine yield contributing characters. The correlation coefficients were determined to find out the inter relationship among the characters studied. Yield per plant was found highly significant and positively correlated with flowers per plant, fruits per plant, fruit length, fruit diameter and individual fruit weight which indicated that yield could be increased by improving a traits. In order to obtain a clear picture of the inter relationship between yield per plant and its components, direct and indirect effects were measured using path coefficient analysis. Fruits per plant showed the highest positive direct effect (0.980) on yield per plant followed by individual fruit weight (0.958). On the other hand, the highest negative direct effect on yield per plant showed by days to first flowering (-0.277) followed by fruit length (-0.141). The characters showed high direct effect on yield per plant indicated that direct selection for these traits might be effective and there is a possibility of improving yield per plant through selection based on these characters. Residual effect was considerably low (0.183) which indicated that characters included in this study explained almost all variability towards yield. Keywords: Correlation coefficients; path coefficient analysis; residual effect DOI: http://dx.doi.org/10.3329/bjpbg.v23i1.9313 BJPBG 2010; 23(1): 13-18